THE ROLE OF DISASTER-RESILIENT VILLAGES SUPPORTING TOURISM IN BADUNG DISTRICT - Made Agus Sugianto (Jurnal Sains dan Teknologi Mitigasi Bencana, 2021)
Badung Regency is a very famous tourist destination to foreign countries. However,most of these tourist destination areas are located in disaster-prone areas. This studyaims to determine the role of disaster-resilient villages in providing security and comfortto tourists visiting tourist objects. This study used a descriptive-analytic method with adesk study design. Disaster Resilient Villages / Kelurahan are villages that have theindependent ability to adapt and face potential disaster threats. Currently, there are 31disaster-resilient villages in Badung Regency, most of which are tourist destinationareas. In disaster-resilient coastal areas, the potential for tsunami disasters, highlandareas are potentially affected by landslides. The prevention and mitigation efforts thathave been carried out by the Badung Regency Government include; build an earlywarning system, install warning signs, carry out disaster simulations and disseminateinformation to the public.